Teacher's Efforts In Improving Early Childhood's Symbolic Thinking Abilities Through Geometry Play Activities - Aris Suziman; Rosnawati Rosnawati; Ode Yahyu Herliani Yusuf (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
Symbolic thinking ability is one of the essential cognitive aspects that need to be developed from an early age. This study aims to explore the efforts of teachers in improving children's symbolic thinking skills through geometry play activities at TK Sangiantina, Kabaena Tengah Subdistrict, Bombana Regency. The research employs a qualitative approach with a classroom action research design. The research subjects consisted of 20 children from TK Sangiantina. Data collection was conducted through observation, documentation, and evaluation of geometry play activities. he evaluation results regarding the enhancement of symbolic thinking skills through geometry play activities indicate significant improvement. This is evident from the comparison of initial observation results before and after the intervention. Before the intervention, the percentage was 45% (9 out of 20 children), with 2 children categorized as "Developing Very Well" (BSB) and 7 children as "Developing as Expected" (BSH). In Cycle I, the percentage increased to 60% (12 out of 20 children), with 5 children in the BSB category and 7 in the BSH category. In Cycle II, the percentage rose further to 80% (16 out of 20 children), with 9 children categorized as BSB and 7 as BSH. In conclusion, symbolic thinking skills in Group B children can be enhanced through geometry play activities.